The fantasy of reality : on the design drawings of Álvaro Siza Vieira - Duarte, João Miguel Couto, 1966- (2021)
Fantasy – understood as a fiction, an extravagance, or a reverie – is often perceived as being at odds with reality, a way of eluding its own contingencies, with reality and fantasy arguably existing in different spheres. But fantasy is also perceived as being intertwined with reality for always being rooted in it, with reality and fantasy accordingly being distinct from each other only on the surface. This paper aims to discuss the fantasy that would seem to pervade some of the design drawings made by the architect Álvaro Siza Vieira. Siza Vieira has always relied on the drawing to immerse himself in and to amble through the architectural objects as they are being defined. Many of the said drawings establish a more immediate relationship with what they purport to represent; others, on the contrary, deliberately avoid such a relationship – reality instead appears altered, if not to say distorted, often being populated with weird figures, as if the architectural object being defined were part of a fantasy. Nevertheless, these drawings also allow for an understanding of their objects, and the place of fantasy in Siza Vieira’s design process is one deserving of assessment. With a nod to the title of one of his books, perhaps one can say that Siza Vieira finds in fantasy a way ‘To Imagine the Evidence’ of his architecture.